Status Resistensi Larva Aedes sp Sebagai Vektor Dengue Terhadap Insektisida Malation di Kota Bengkulu (Berita Kedokteran Masyarakat (BKM), 2020)
AbstractPurposes: Dengue is emerging as a serious public health problem globally. The primary strategy to control dengue is by reducing the vector population using insecticides. Malathion has been massively used since the 1990s in dengue control programs. As there is no effective dengue drug or safe vaccine available, vector control remains the most effective intervention to reduce incidence and prevent transmission and outbreak. This study determined resistance status to malathion of Aedes sp larvae from Jalan Gedang Village, Bengkulu City (dengue endemic areas). Methods: This study used experimental with post-control only design. Aedes sp eggs were collected by ovitraps and colonized to larvae stage. Susceptibility test of larvae to the malathion was estimated using standard WHO. Results: Mortality of larvae Aedes sp after 24 hours with multiple concentration of malathion indicative of highly resistant (p=0.001). Conclusions: Continued testing to insecticide resistance in dengue vector is important to prevention of increased incidence of dengue. In order to reduce the development of insecticidal resistance, it recommended insecticides of different chemical structures be applied in rotation.